2001
DOI: 10.1074/jbc.m006404200
|View full text |Cite
|
Sign up to set email alerts
|

The C Terminus of Mammalian Phospholipase D Is Required for Catalytic Activity

Abstract: The activity of phospholipase D (PLD) is regulated by a variety of hormonal stimuli and provides a mechanistic pathway for response of cells to extracellular stimuli. The two identified mammalian PLD enzymes possess highly homologous C termini, which are required for catalytic activity. Mutational analysis of PLD1 and PLD2 reveals that modification of as little as the Cterminal threonine or the addition of a single alanine attenuates activity of the enzyme. Protein folding appears to be intact because mutant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Our studies on rat PLD1 (rPLD1) showed that there is an interdomain association between the N-and C-terminal halves of the molecule and this is important for the catalytic activity (25,26). Another domain essential for the catalytic activity of PLD is located at the C terminus of the enzyme, and deletion of the last amino acid of rPLD1 abolishes its enzymatic activity (27,28,30). Besides the motifs essential for the catalysis, domains important for the PKC and Rho responses have been mapped to the N-terminal and C-terminal regions of the enzyme, respectively (29 -32).…”
Section: Phospholipase D (Pld)mentioning
confidence: 99%
“…Our studies on rat PLD1 (rPLD1) showed that there is an interdomain association between the N-and C-terminal halves of the molecule and this is important for the catalytic activity (25,26). Another domain essential for the catalytic activity of PLD is located at the C terminus of the enzyme, and deletion of the last amino acid of rPLD1 abolishes its enzymatic activity (27,28,30). Besides the motifs essential for the catalysis, domains important for the PKC and Rho responses have been mapped to the N-terminal and C-terminal regions of the enzyme, respectively (29 -32).…”
Section: Phospholipase D (Pld)mentioning
confidence: 99%
“…It has also been demonstrated that deletion of the last four amino acids of rat PLD1 abolishes PLD activity of this protein, although substitution of these amino acids to other charged or less hydrophobic amino acids restored some PLD activity to these proteins and addition of protein with an intact C-terminus restored full PLD activity [40]. The importance of these C-terminal amino acids has been confirmed by a complementary analysis of human PLD1, which also established that PLD activity could be partially restored to deletion mutants by the addition of a peptide consisting of the six C-terminal amino acids [41]. These data would indicate that the C-terminus, absent in PLD1a2 and PLD1b2, should have a role in catalytic activity and therefore that PLD1a2 and PLD1b2 might be predicted to have no PLD activity at all.…”
Section: C-terminus Of Pld1 Isoforms Is Involved In Catalysismentioning
confidence: 57%
“…Secondly, the C-terminus has a strong influence on the catalytic activity of PLD1. Deletion of the C-terminus destroys PLD1 activity ( Figure 6C, [16,[39][40][41]46]) ; however, it appears that the ten amino acids found in PLD1a2 and PLD1b2 are sufficient to restore partial activity to PLD1a or PLD1b that lack the C-terminal 113 amino acids. However, catalytic activity does not appear to influence endosomal localization.…”
Section: Discussionmentioning
confidence: 99%
“…One region is conserved sequence III and another is the extreme C-terminus, since limited mutations of these sequences abolish catalysis (Sung et al 1999b;Xie et al 2000b;Liu et al 2001). The C-terminal four amino acids are conserved in PLD1 and PLD2 and are similar to those in putative PLDs from C. elegans and D. melanogaster, but deviate from those in fungi, bacteria and plants (Fig.…”
Section: By Permission Of the Authors And Publishermentioning
confidence: 99%